From Laboratory Studies to Clinical Trials: Temozolomide Use in IDH-Mutant Gliomas - Xueyuan Sun; Sevin Turcan (Cells, 2021)
In this review, we discuss the use of the alkylating agent temozolomide (TMZ) in the treatment of IDH-mutant gliomas. We describe the challenges associated with TMZ in clinical (drug resistance and tumor recurrence) and preclinical settings (variabilities associated with in vitro models) in treating IDH-mutant glioma. Lastly, we summarize the emerging therapeutic targets that can potentially be used in combination with TMZ.